Community acquired pneumonia in Malaysia: is Streptococcus pneumoniae an important pathogen? - Mohd Taib, Niazlin; Ban, Andrea Yu-Lin; Abd. Manap, Roslina; Jamal, Farida Fatema @ Farida; Che Isahak, Che Ilina (Academic Journals, 2012)
Previous data on etiological agents isolated from adult patients with community acquired pneumonia (CAP) in Malaysia has showed very low percentage of Streptococcus pneumoniae. Thus, we used immunochromatography test (ICT) and real-time polymerase chain reaction (PCR) in addition to conventional culture methods for S. pneumoniae detection. We found that the detection rate was highest by real time PCR reaction (50%) in contrast to 10% by ICT, 2% from blood and 0% from sputum cultures. This molecular method had contributed to a rise in percentage of S. pneumoniae detection accounting for 51.1% of all etiological cases in CAP and the second commonest organism after Chlamydophila pneumoniae (63.8%), followed by M. pneumoniae (27.7%) and L. pneumophila (17%). We have also found that 10.6% of the etiological agents of CAP were not known indicating that other specific organisms including viruses have not been identified. Both ICT and PCR demonstrated sensitivities of 100%, with specificities of 91.3 and 55.6%, respectively, using culture techniques as the “gold standard”. Thus from this finding, they will become potential tools in the future for the diagnosis of S. pneumoniae in CAP, for the epidemiological importance and prevention as well as for early antibiotic management.